The Problem of Professional Preparation of the Future Primary School Teachers in Pedagogical Heritage of K.Ushynskyi - Shkvyr, Oksana (Pedagogical Discourse, 2014)
The attention in the article is accentuated to the problem of qualitative renovation of the system of professional preparation of the future primary school teachers under the conditions of graded education, the necessity of study of K.Ushynskyi’s works in the context of solving of the mentioned problem has been reasoned. Scientific groundworks of K.Ushynskyi as for the system of professional preparation of the future primary school teachers have been cleared up in the publication, his pedagogical views to the social meaning of work of a school pedagogue, the aim, content and the ways of future teachers’ preparation, peculiarities of different types of educational establishments, which should prepare future primary school teachers have been investigated. Involvement of the pedagogue in the working out of the questions of the graded education of the future teachers of junior schoolchildren has been found out: the first grade – preparatory teachers’ school, the second – teachers’ seminary. General educational, special and pedagogical aspects of such preparation have been cleared out. The conclusions about the fact that K.Ushynskyi for the first time worked out and proved the necessity of anthropological approach to the preparation of the future teacher, and namely the primary school teacher, have been made.